House of the dragon. 1 [videorecording (DVD)] - Condal, Ryan J.; Martin, George R. R. (Warner Bros. Entertainment Inc., 2022)
"Set 200 years before the events of Game of Thrones, the series finds the Targaryens ruling over the Seven Kingdoms -- and on the brink of civil war within their own house. Prior to the birth of a son, King Viserys sent shockwaves through the kingdom and declared his daughter, Rhaenyra, his heir. Once a healthy boy entered the picture, plans were afoot to make sure she would never sit on the Iron Throne. Now, with schemes hatched on both sides -- and the kingdom in the balance -- viewers will see the house that dragons built and learn how they tore it all down" --Container.